FORMATION OF OUTPUT YIELD OF GREEN BEANS DEPENDING ON SCHEME AND DENSITY OF PLANTING IN CONDITIONS OF STEPPE OF THE UKRAINE - V. M. Chernetskiy; O. O. Kostyuk; О. А. Vlasuk (Овощи России)
Under the conditions of Steppe  of the Ukraine during 2010-2012 a scheme  of planting and plant population of beans played a big role on the formation of a yield of green  beans variety Ukrainian Sloboda.   The highest  yield of cv. Ukrainian Sloboda; 13.5 t / ha; was obtained when the density of planting was 148;1 thousand plants/hectare  and the scheme of planting was 45х15.